2005
DOI: 10.1111/j.1365-3016.2005.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of reporting maternal in‐hospital diagnoses and intrapartum procedures in Washington State linked birth records

Abstract: While the impact of maternal morbidities and intrapartum procedures is a common topic in perinatal outcomes research, the accuracy of the reporting of these variables in the large administrative databases (birth certificates, hospital discharges) often utilised for such research is largely unknown. We conducted this study to compare maternal diagnoses and procedures listed on birth certificates, hospital discharge data, and birth certificate and hospital discharge data combined, with those documented in a stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 27 publications
9
138
0
Order By: Relevance
“…This approach improves sensitivity (e.g., from 52% to 86%) compared to relying on birth certificate data alone. 14 Table S1; Supplementary Data are available online at www .liebertpub.com/jwh) were based on ACOG recommendations 20 and included post-term pregnancy ( ‡ 41 completed weeks of gestation), diabetes, hypertension, preeclampsia, eclampsia, prelabor rupture of membranes, maternal heart disease, and others. Inductions with no documented indication other than macrosomia (2%) were categorized as elective because there is scant evidence that such inductions improve outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach improves sensitivity (e.g., from 52% to 86%) compared to relying on birth certificate data alone. 14 Table S1; Supplementary Data are available online at www .liebertpub.com/jwh) were based on ACOG recommendations 20 and included post-term pregnancy ( ‡ 41 completed weeks of gestation), diabetes, hypertension, preeclampsia, eclampsia, prelabor rupture of membranes, maternal heart disease, and others. Inductions with no documented indication other than macrosomia (2%) were categorized as elective because there is scant evidence that such inductions improve outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10][11] While studies have examined the impact of specific initiatives at single institutions or health care systems, there is little information available about general trends in induction in the United States in recent years. Two studies reported that early-term 12 and late preterm 13 induction rates increased through 2006, but these studies relied on birth certificate data, which miss many inductions 14 and do not reliably distinguish elective from indicated inductions. 15 A recent study of specialty hospitals was the first to provide nationally representative data, reporting an 11% increase in induction from 2006 to 2010.…”
mentioning
confidence: 99%
“…Use of the combined birth certificate and hospital discharge data has been found to be more accurate for perinatal outcomes, compared with birth certificate data alone. 9,10 Various maternal sociodemographic characteristics have been shown to be associated with maternal obesity and were evaluated as potential confounders in this study. Maternal education was categorized as high, average, or low on the basis of age and years of education.…”
Section: Methodsmentioning
confidence: 99%
“…Linking birth data to hospital admission data has provided greater sensitivities of maternal morbidity diagnoses, birth outcomes and intrapartum procedures without any increase in false positives. [32][33][34][35][36] Studies in the US have demonstrated that combining information from birth certificates and confidential questionnaires yielded higher estimates of maternal smoking prevalence. 22,26 Little is known in Australia about the extent to which linking birth data with hospital admission data improves the identification of pregnant smokers and its potential impact on estimates of maternal smoking prevalence, and risks of smokingrelated adverse pregnancy outcomes including placental abruption, preterm delivery, stillbirth and low birthweight.…”
mentioning
confidence: 99%